Sistem Pendukung Keputusan Seleksi Calon TKI ke Jepang dengan Metode Topsis - Faisal, Muhamad Fandi; Suryopratomo, Anggit; Ishak, Kanda M. (Ma'soem University, 2024)
The purpose of the study is to shorten the time and facilitate the selection process of prospective Indonesian workers and create a decision support system based on performance appraisal criteria in the selection of prospective workers so as to obtain objective results, as well as to minimize errors from the selection process of prospective Indonesian workers to work in Japan at PT. Sarekah Insan Atama Foundation. This thesis uses a Decision Support System with the TOPSIS method then a system development method using OOAD (object-oriented analysis and design). The results showed that the creation of this website-based application can facilitate the CTKI Selection assessment process to work in Japan at PT. Sarekah Insan Atama Foundation.